EVALUASI LINGKUNGAN PENGENDALIAN DALAM PERTUMBUHAN USAHA YANG CEPAT: STUDI KASUS PADA PT G - Kurniawati, Heny (Binus Business Review, 2011)
The effective Internal Control System plays fundamental role in a strong corporate governance. One important component of COSO Internal Control is Control Environment. This case study try to describe and discuss about the strengths and weaknesses of Control Environment, one of the Internal Control componen, of company G, a financial institution and how rapid bussiness changes affect the existing control environment. The result of this study showed that rapid business changes and the failure to identify and manage risks of the changes affect the strengths of existing control environment and heighten the weaknesses of control environment.Â